1984
DOI: 10.1093/oxfordjournals.eurheartj.a061546
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory electrocardiographic findings in young athletes between 14 and 16 years of age

Abstract: Ambulatory electrocardiographic recordings were obtained from 35 male athletes between 14 and 16 years old, and from 35 male non-athlete controls of the same ages, in order to determine the effects of regular physical training on cardiac electrical activity. In the young athletes, the heart rates were significantly (P less than 0.01) lower than in the nonathletes. Sinus intervals over 2.00 s were present in five athletes (14%) and one control (3%). First-degree atrioventricular block was detected in eight athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…The minimum, maximum, and mean heart rates during 24-hour ambulatory electrocardiographic monitoring were within the normal values previously reported in older children and young adults [3,7,14,16,18]. No patient had been receiving amiodarone.…”
Section: Resultssupporting
confidence: 80%
“…The minimum, maximum, and mean heart rates during 24-hour ambulatory electrocardiographic monitoring were within the normal values previously reported in older children and young adults [3,7,14,16,18]. No patient had been receiving amiodarone.…”
Section: Resultssupporting
confidence: 80%
“…However, these findings were limited to a single‐center experience and were not in keeping with the results of old studies performed in the 1980s and 1990s, which demonstrated no differences in the VA burden at 24‐hour ambulatory electrocardiographic monitoring between athletes and sedentary individuals 6, 7, 8, 9, 10, 11. Moreover, these previous investigations focused on the number and complexity of VAs without characterizing the morphologic features of premature ventricular beats (PVBs), a parameter that may help to identify the site of origin of the arrhythmia and the possible underlying myocardial substrate 12…”
Section: Introductionmentioning
confidence: 73%
“…In this study, most athletes with VAs had no evidence of underlying structural abnormalities, the arrhythmias tended to decrease after detraining, and the follow‐up was uneventful: all these findings are consistent with the concept that VAs may be considered a feature of the “athlete's heart.”4, 5 Moreover, Palatini et al compared 40 endurance athletes with 40 sedentary individuals and found that the prevalence of complex VAs at ambulatory electrocardiographic monitoring was higher in trained individuals 10. Other studies comparing the prevalence of VA at 24‐hour ambulatory electrocardiographic monitoring in healthy athletes versus sedentary individuals disproved the concept of a proarrhythmic effect of sports activity by demonstrating that only a minority of athletes exhibited frequent or complex VAs with a prevalence that did not differ with that of their sedentary counterpart6, 7, 8, 9, 11 (Table S4). In addition, Delise et al reported that the proportion of athletes with VAs who showed a reduction in the arrhythmic burden during follow‐up was similar in a group undergoing detraining and in a group who continued training 21…”
Section: Discussionmentioning
confidence: 99%
“…Variations from sinus rhythm Ambulatory electrocardiographic monitoring on normal healthy infants and children of all ages [10][11][12][13][14] has confirmed that regular uninterrupted sinus rhythm may be punctuated from time to time by a variety of rhythm changes which could potentially be regarded as abnormal. The frequency with which these changes occur emphasises the importance of understanding the range of normal variation of heart rhythm in children and of correlating symptoms with rhythm change when investigating unusual events.…”
Section: Qrs Complexmentioning
confidence: 98%